Public Expenditure Reviews in Science, Technology, and Innovation : A Guidence Note - Correa, Paulo (World Bank Group, Washington, DC, 2015)
This Guidance Note lays out a framework for the assessment of science, technology, and innovation (STI) expenditures in developing countries, with an emphasis on their contribution to economic development.